Efectos de la herculizacion frente a los aireadores en banano - Suárez Morocho, Luis Alberto (2012)
In the place Caña Quemada, located at 4,5 km El Guabo-Pasaje road, belonging to the Pasaje county El Oro province, was studied The Effects of the herculization in front of the aerators in banana tree on the development and banana tree production with the following objectives: 1. To determine the effects of the herculization in the physical and chemical part of the soil; 2. To establish the benefits in the yield of the production of the plant. Five treatments were studied, T1, 1 pass of Hercules + aerators; T2, 2 passes of Hercules + aerators; T3 3 passes of Hercules in half moon; T4. Aerators; T5 absolute witness. The studied variables were, levels of potassium in the soil, porosity percentage at the beginning and the end., Capacity of cationic exchange at the beginning and the end, percentage of organic matter at the beginning and the end. height of the son at 30, 60 and 90 days, number of leaves at 30, 60 and 90 days, pseudo stem width at 30, 60 and 90 days, height of the son at birth, days at birth, foliar area at birth, initial and final radicular volume , number of hands per bunch, bunch weight and ratio. The Design Blocks al Random was used with five treatments and four replications. In the analysis of the agronomic variables, plant height, width of the stem, number of leaves per plant and days to the blooming, there was not difference among the averages of treatments, but as referring to the number of hands per bunch, weight of the bunch, exportable fruit, 43- pound boxes obtained in the rehearsal and the Ratio, the technology of soil removal and the complementary aeration with terciarias were very efficient. The number of hands per bunch, weight of the bunch, exportable fruit and ratio, experienced significant changes with the agricultural works of aerators and herculization of the soil. For the number of hands per bunch, the increments reached with the treatments varied among 34,9 to 68,62%. With three passes of the Hercules in half moon shape, the biggest weight in the bunch was reached and in the processing of the fruit to the Hercules' treatment Three passes in half moon shape reached the biggest quantity in exportable fruit, 43 pounds boxes and a ratio of 1,78.